Improvement of the Ability to Write Exposition Text Using Contextual Learning Model of Students at VIII2 Class SMP Muhammadiyah Ambon - Vivin, Ade; Rumalean, Iwan; Tabelessy, Novita (Universitas Pattimura, 2022)
Education is crucial for the development of the nation's youth, as it enables the cultivation of bright, skillful, and well-rounded generations. A nation's requisite intelligence encompasses both cognitive and interpersonal dimensions. In this instance, public speaking constitutes an engaging and instructive communicative endeavor, employing succinct, dense, and lucid language. Effective public speaking can leave a favorable impression on the audience. Given that a relationship between the speaker and the audience is inevitable in public speaking, it is essential to prepare well to attain the intended outcome. Consequently, an enhanced learning model is requisite to augment students' public speaking abilities, one approach being the use of the Time Token learning paradigm. This study aims to enhance public speaking skills through the Time Token learning approach in class VIII5 at SMP Negeri 17 Ambon. This study employs classroom action research.